Why is the Influence of Servant Leadership on Affective Commitment to Change Insignificant? Proposing Objective Workplace Spirituality as the Mediator - Sindu Prawira (Petra International Journal of Business Studies, 2021)
The ability to quickly adapt to change has been one of the mandatory requirements for every organization to succeed in this disruptive era. While commitment to change is the most desirable attitude when an organization faces major changes, an affective commitment to change is the dominant dimension of commitment to change. On the other hand, leadership is known as one of the most important antecedents of commitment to change. However, researches on this relationship have not been conclusive. Using the affect theory of social exchange and servant leadership theory, this theoretical review argues that the study method, type of exchange structure in the research context, and the need for mediation are the three main reasons for the research gap. This literature review proposes objective workplace spirituality as the mediator between servant leadership and affective commitment to change relationships.